2021
DOI: 10.3389/fmed.2021.647268
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy Between Trifocal and Bifocal Intraocular Lens Among Patients Undergoing Cataract Surgery: A Systematic Review and Meta-Analysis

Abstract: The comparative efficacy of trifocal and bifocal intraocular lenses (IOLs) remained uncertain among patients undergoing cataract surgery. A systematic review and meta-analysis was performed to answer this question. PubMed, Cochrane Library and Embase were searched to capture relevant randomized controlled trials (RCTs). Visual acuity (VA) and patient's satisfaction were regarded as primary outcomes. Secondary outcomes included residual sphere, spherical equivalence, residual cylinder, posterior capsular opacif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(161 reference statements)
1
4
0
Order By: Relevance
“…A 2021 meta-analysis [5] comparing trifocal and bifocal IOLs was consistent with existing literature, showing that trifocal IOLs offer similar distance and near vision, and superior intermediate vision, compared to bifocals. It remains uncertain whether contrast sensitivity differs significantly between trifocal and bifocal designs, though most authors consider the loss of contrast sensitivity in both groups to be minor [6].…”
Section: Multifocal Intraocular Lensessupporting
confidence: 79%
“…A 2021 meta-analysis [5] comparing trifocal and bifocal IOLs was consistent with existing literature, showing that trifocal IOLs offer similar distance and near vision, and superior intermediate vision, compared to bifocals. It remains uncertain whether contrast sensitivity differs significantly between trifocal and bifocal designs, though most authors consider the loss of contrast sensitivity in both groups to be minor [6].…”
Section: Multifocal Intraocular Lensessupporting
confidence: 79%
“…After splitting the diffractive MIOLs into bifocal and trifocal IOLs, the trifocal IOLs showed an improvement in UDVA when compared to bifocal IOLs. However, no significant differences were identified between trifocal and bifocal IOLs for distant VA in patients without previous corneal refractive surgery ( 24 ). Thus, further studies are required to demonstrated this clearly.…”
Section: Discussionmentioning
confidence: 94%
“…Trifocal and bifocal IOLs are designed to provide three and two focal points, respectively. Previous studies have demonstrated that patients implanted with trifocal IOLs may achieve better intermediate visual acuity (VA), and comparable distance and near VA than bifocal IOLs ( de Silva et al, 2016 ; Shen et al, 2017 ; Zhang et al, 2021 ). Pre-existing corneal and residual astigmatism are important factors limiting the application of multifocal IOLs ( Woodward et al, 2009 ; de Vries et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%